Upaya Peningkatan Pengetahuan Tentang HIV/AIDS pada Ibu Rumah Tangga di Dusun Sempon Cangkringan Sleman Yogyakarta - Khadijah, Sitti; Palifiana, Dheska Arthyka (Universitas Respati Yogyakarta, 2019)
Background: The National AIDS Commission states that the low knowledge of housewives in preventing HIV/AIDS is one of the factors causing the increasing of HIV/AIDS case in housewife. Research Objective: The purpose of the study is to provide knowledge about HIV/AIDS so that there is increasing knowledge of housewife on HIV/AIDS. Methods: The activities was given by counseling of HIV/AIDS with lecture method, to have question and answer session and evaluation methods. The data collection before and after counseling was using questionnaires with technical data analysis using paired sample t-test. Results: Participants are characterized by age; the result showed themajority aged that more than 35 years were 20 people (90.9%). Participantâ€™s education were majority at secondary education levelas many as 12 people (54.5%). Based on work, participants were majority not working or housewife as many as 12 people (54.5%). The result of pretest showed the level of knowledge in good category as many as nine people (40.9%), and post-test result showed that there was an increasing number of participants in good category as many as 16 people (72.7%). The result of analysis by using paired sample ttest with p-value = 0.000 (p <0.05).Â Conclusion: There is a difference of knowledge before and after counseling, so that it can be concluded that HIV/AIDS counseling was effective to increase knowledge to housewives in Sempon sub-village, Cangkringan SlemanKeywords: Knowledge, HIV/AIDS, HousewivesÂ